HUBUNGAN AKTIFITAS FISIK, RIWAYAT ORANG TUA DAN POLA MAKAN DENGAN KEJADIAN OBESITAS PADA ANAK DI SEKOLAH DASAR - Elsi Rahmadani; Pawiliyah Pawiliyah; Novi Ade Suryani; Suryani Suryani (KOLONI, 2022)
The number of overweight children aged 5-19 years has increased on every continent from 1990-2016, the highest was in the United States with a prevalence in 2016 of 41.86% (UNICEF, 2019). The purpose of this study was to determine the relationship between physical activity, and diets with the cases of obesity in children. The method used was an analytical research design with a cross sectional approach. The sample in this study was 52 school-age children in grades 4 and 5 at the State Elementary Islamic 2 in Bengkulu using a total sampling technique. This study used SPSS with a chi-square bivariate statistical test with a value of =<0.05. The results of univariate analysis that more than half of the respondents 51.9% or 27 respondents have moderate physical activity, more than half of the respondents 65.4% or 34 respondents have a pattern eat well, most of the respondents 71.2% or 37 respondents are not obese. The results of the bivariate analysis showed that there was a relationship between physical activity, and diets with the incidence of obesity in children at the State Elementary Islamic 2 in Bengkulu (p : 0.000). There is a relationship between physical activity, and diets with the cases of obesity in children at State Elementary Islamic 2 in Bengkulu (p: 0.000. The researcher suggests for schools to be more active in conducting counseling or education about childhood obesity. Keywords: physical activity, parental history, diet, obesity